KEY FACTORS FOR ENHANCING THE EFFECTIVENESS OF WOMEN’S INNOVATIVE THINKING IN THE PROCESSES OF RENEWAL IN UZBEKISTAN - To‘yeva, Muhayyo (Journal of Fundamental Studies, 2026)
The purpose of this study is to identify the key factors for enhancing the effectiveness of women’s innovative thinking in the context of renewal processes in Uzbekistan. The research employs historical-logical, comparative, and systemic analysis methods, based on philosophical, social, and normative sources to comprehensively examine the issue. The findings indicate that the development of women’s innovative thinking is closely associated with quality education, the strengthening of gender equality principles, state support mechanisms, the advancement of digital technologies, and the socio-cultural environment. In addition, national values and ethical principles play a significant role in shaping innovative thinking. The study concludes that enhancing women’s innovative potential is a crucial condition for ensuring societal modernization and sustainable development.